Modified Five Parameters Weibull-Dal Distribution with its Statistical Properties - Nawaz, Shahbaz; Md Yusof, Zahayu; Okwonu, Friday Zinzendoff (Harbin Gongye Daxue Xuebao, 2021)
New lifetime model is generated from Weibull-G family of distributions introduced by Weibull-DAL distribution. Properties of the modified new model Weibull-DAL (W-DAL) distribution with five parameters are introduced investigated. For example, dependability qualities, extension of the density, explicit formulations for ordinary and incomplete moments and moment generating functions, as well as quantile functions and probability-weighted moments, may be accomplished on these models. To estimate model parameters, we utilise the greatest likelihood method. There will be a set of MLEs generated for each model